Salvage dual graft living donor liver transplantation after major hepatectomy - Kim, Joo Dong; Choi, Dong Lak; Han, Young Seok (Annals of surgical treatment and research, 2014)
Salvage living donor liver transplantation (LDLT) after major hepatectomy has been considered a challenging procedure due to operative complexity. We report a successful case of salvage dual graft LDLT after right hepatectomy. A 48-year-old male was transferred to Daegu Catholic University Medical Center because of duodenal variceal bleeding. He underwent right hepatectomy due to hepatocellular carcinoma four years prior. We performed LDLT with dual graft from his wife and sister. During operation, portal vein anastomosis of the right lobe graft was performed using an interposing cadaveric iliac vein graft and the right gastroepiploic artery was anastomosed to the hepatic artery of the left lobe graft. Adequate graft inflow was demonstrated by postoperative imaging studies. He has been doing well with normal graft function for 31 months. Salvage dual graft LDLT could be undertaken successfully in patients with prior major hepatectomy under accurate preoperative planning and proper surgical techniques.